Numerical study of the behavior of intermeshed steel connections under mixed-mode loading. (September 2019) - Shemshadian, Mohammad E.; Le, Jia-Liang; Schultz, Arturo E.; McGetrick, Patrick; Al-Sabah, Salam; Laefer, Debra F.; Martin, Anthony; Hong, Linh Truong; Huynh, Minh Phuoc
Abstract: In recent years, advanced manufacturing techniques, such as high-definition plasma, water jet, and laser cutting, have opened up an opportunity to create a new class of steel connections that rely on intermeshed (i.e. interlocked) components. The main advantage of this type of connection is that they do not require either welding or bolting, which allows faster construction. Although the interest in intermeshed connections has increased in recent years, the mechanical behavior of these connections has not been fully understood. This paper presents a numerical study on the ultimate load capacity failure modes of intermeshed connections under mixed-mode loading. The experimental behavior of the connection components is also investigated through a series of tests. The study considers a recently developed intermeshed connection for beams and columns. The numerical simulations were performed by using a commercially available 3D finite element software package. By considering different types of mixed mode loading, interaction diagrams of axial, shear, and moment capacities of the intermeshed connection were obtained. The results indicated that there exists an intricate interaction among axial, shear, and moment capacities, which arises from the intermeshed configuration of the flanges and web. For each interaction diagram, the corresponding failure mechanism was analyzed. The simulated interaction between axial, shear, and moment capacities were further compared with the provision of the current design codes. While the intermeshed connection studied here showed promise for gravity loading, further study is needed to ensure alignment of the flanges so as to avoid axial and/or flexural failures. Highlights: The intermeshed steel connection exhibits excellent shear resistance. Axial and flexural behavior are affected by the alignment of the intermeshed flanges. The presence of shear has a significant influence on axial and moment capacities. P-M-V interactions in existing codes are not applicable to the intermeshed connection. This connection could serve in gravity frames if flange alignment could be maintained.